Molecular Outcome, Prediction, and Clinical Consequences of Splice Variants in COL1A1, Which Encodes the proα1(I) Chains of Type I Procollagen. Issue 7 (July 2015) - Schleit, Jennifer; Bailey, Samuel S.; Tran, Thao; Chen, Diana; Stowers, Susan; Schwarze, Ulrike; Byers, Peter H.
<x xml:space="preserve">Abstract</x> We examined genotypes and phenotypes of 243 individuals with osteogenesis imperfecta (OI) whose mutations within COL1A1 altered mRNA splicing. We observed consistent splice outcomes and OI phenotypes in individuals whose mutations substituted the last guanine of COL1A1 introns to adenine when these substitutions were preceded by guanines. In contrast, similar substitutions of the first intron guanine resulted in multiple splice outcomes, often with multiple observed in the same individual, and highly variable OI phenotypes.